Mining-Induced Failure Criteria of Interactional Hard Roof Structures: A Case Study - Wenlong Shen (Energies, 2019)
Due to the additional abutment stress, interactional hard roof structures (IHRS) affect the normal operation of the coal production system in underground mining. The movement of IHRS may result in security problems, such as the failure of supporting body, large deformation, and even roof caving for nearby openings. According to the physical configuration and loading conditions of IHRS in a simple two-dimensional physical model under the plane stress condition, mining-induced failure criteria were proposed and validated by the mechanical behavior of IHRS in a mechanical analysis model. The results indicate that IHRS, consisting of three interactional parts—the lower key structure, the middle soft interlayer, and the upper key structure—are governed by the additional abutment stress induced by the longwall mining working face. The fracture of the upper key structure in IHRS can be explained as follows: Due to the crushing failure, lower key structure, and middle soft interlayer yield, the action force between the upper and lower key structures vanishes, resulting in fracture of the upper key structure in IHRS. In a field case, when additional abutment stress reaches 7.37 MPa, the energy of 2.35 × 105 J is generated by the fracture of the upper key structure in IHRS. Under the same geological and engineering conditions, the energy generated by IHRS is much larger than that generated by a single hard roof. The mining-induced failure criteria are successfully applied in a field case. The in-situ mechanical behavior of the openings nearby IHRS under the mining abutment stress can be clearly explained by the proposed criteria.